Control and Prevention of Epizootic Lymphangitis in Mules: An Integrated Community-Based Intervention, Bahir Dar, Ethiopia - Duguma, Bojia E.; Tesfaye, Tewodros; Kassaye, Asmamaw; Kassa, Anteneh; Blakeway, Stephen J. (Frontiers in Veterinary Science, 2021)
From 2010 to 2017 as part of a wider animal welfare programme, The Donkey Sanctuary piloted an integrated, community-based model for the control and prevention of Epizootic lymphangitis (EZL) in cart mules in Bahir Dar, Ethiopia. Stakeholders included muleteers, service providers, and transport and animal health regulatory authorities. Interventions included muleteer education, wound prevention, harness improvement, animal health professional training, treatment of early EZL cases, euthanasia for advanced cases, and review of transport services and traffic guidelines. The project followed a participatory project management cycle and used participatory learning and action tools to facilitate stakeholder engagement and ownership. Participatory and classical epidemiology tools were employed to raise and align stakeholder understanding about EZL for effective control and prevention, and to evaluate the progress impact of the model through annual prevalence surveys. During the intervention the annual prevalence of EZL reduced from 23.9% (102/430) (95%CI: 19.8%-27.0%) in 2010 to 5.9% (58/981) (95% CI: 4.4%-7.4%) in 2017, and wound prevalence from 44.3% in 2011 to 22.2% in 2017, trends in the reduction of the prevalence maintained in the face of a mule population that increased from 430 in 2010 to c.1500 in 2017. While non-governmental organisation-led interventions can facilitate change by trialing new approaches and accessing new skills and resources, sustainable change requires community ownership and strengthening of service provision systems. To this effect, the project raised muleteer competence in mule husbandry and EZL prevention strategies; strengthened veterinary competence; facilitated more mule-friendly traffic, transport and waste disposal guidelines and practices; supported mule-community byelaws to control EZL; and established a supportive network between stakeholders including trusting relationships between muleteers and veterinary services. To advance the intervention model in other endemic areas, we recommend elucidation of local epidemiological factors with other stakeholders prior to the intervention, early engagement with veterinary and transport service regulatory authorities, early development of byelaws, exploration of compensation or insurance mechanisms to support euthanasia of advanced cases, and additional social, economic, and epidemiological investigations. In line with the OIE Working Equid Welfare Standards, we suggest that integrated community-based interventions are useful approaches to the control and prevention of infectious diseases.